Keeping clean water clean in a Malawi refugee camp: a randomized intervention trial - Roberts Les; Chartier Yves; Chartier Oana; Malenga Grace; Toole Michael; Rodka Henry (The World Health Organization, 2001)
OBJECTIVE: This study was undertaken to assess the ability of a water container with a cover and a spout to prevent household contamination of water in a Malawian refugee camp. METHODS: A randomized trial was conducted in a refugee population that had experienced repeated outbreaks of cholera and diarrhoea and where contamination of water in the home was found to be a significant cause of cholera. Four hundred Mozambican refugee households were systematically identified and followed over a 4-month period, one fourth of the households were randomly assigned to exclusively use the improved container for water collection. FINDINGS: Water flowing from the source wells had little or no microbial contamination although the water collectors quickly contaminated their water, primarily through contact with their hands. Analysis of water samples demonstrated that there was a 69% reduction in the geometric mean of faecal coliform levels in household water and 31% less diarrhoeal disease (P = 0.06) in children under 5 years of age among the group using the improved bucket. Regression models examining diarrhoea among under 5-year-olds confirmed the protective effect of the bucket and found that visible faeces in the family latrine and the presence of animals were significantly associated with an increased diarrhoeal incidence in children. CONCLUSION: Household contamination of drinking-water significantly contributed to diarrhoea in this population. Proper chlorination is a less expensive and more effective means of water quality protection in comparison with the improved bucket, but was unpopular and rarely utilized by the camp inhabitants.